The prevalence of conjunctivitis in patients with novel coronavirus (COVID-19) and preventive measures - I.R. Gazizova; Yu.A. Desheva; T.V. Gavrilova; V.A. Chereshnev (РМЖ "Клиническая офтальмология")
I.R. Gazizova1, Yu.A. Desheva1, T.V. Gavrilova2, V.A. Chereshnev2,3 1Institute of Experimental Medicine, St. Petersburg, Russian Federation 2Academician E.A. Vagner Perm State Medical University, Perm, Russian Federation 3Institute of Immunology and Physiology of the Ural Branch of the Russian Academy of Sciences, Ekaterinburg, Russian Federation According to the American Academy of Ophthalmology, coronavirus infection can cause follicular conjunctivitis. However, transmission pathways and conjunctival tropism of SARS-CoV-2 are still disputable. This paper reviews a few studies on the possible involvement of SARS-CoV-2 in ocular surface diseases and ocular defence mechanisms against viruses. More research is needed to describe the presence of viral RNA in tears and to determine whether SARS-CoV-2 is transmitted by the contact with conjunctiva and/or through secrets although conjunctivitis was diagnosed in only a few patients with COVID-19 and only a few patients were positive for SARS-CoV-2 by conjunctival polymerase chain reaction (PCR). Potential transmission of novel coronavirus through the ocular surface is of great concern to ophthalmologists. Considering this, close proximity eye examinations (when physical touch is required) are associated with high risks of SARS-CoV-2 transmission to ophthalmologists. Therefore, examinations should be performed using personal protective equipment. The review of available data will help understand ocular manifestations of SARS-CoV-2 infection and keep preventive measures. Keywords: eye, COVID-19, SARS-CoV-2, coronavirus, ocular manifestations of coronavirus, conjunctivitis, Actipol-M. For citation: Gazizova I.R., Desheva Yu.A., Gavrilova T.V., Chereshnev V.A. The prevalence of conjunctivitis in patients with novel coronavirus (COVID-19) and preventive measures. Russian Journal of Clinical Ophthalmology. 2020;20(2):92–96. DOI: 10.32364/2311-7729-2020-20-2-92-96.